On the N=4, d=4 pure spinor measure factor - Azevedo, Thales (Springer, 2015)
In tins work, we obtain a simple measure factor for the lambda and theta zero-mode integrations in the pure-spinor formalism in the context of an N = 4, d = 4 theory. We show that the measure can be defined unambiguously up to BRST-trivial terms and an overall factor, and is much simpler than (although equivalent to) the expression obtained by dimensional reduction from the N = 1, d = 10 measure factor. We also give two explicit examples of how to obtain the dual to a vertex operator using this measure.
Keywords: Superstrings and Ileterotic Strings; BRST Symmetry; Extended Supersymmetry